2017
DOI: 10.1080/20009666.2017.1379854
|View full text |Cite
|
Sign up to set email alerts
|

An extensive chronic aortic dissection presenting with acute embolic stroke

Abstract: Herein, we present a rare case of extensive chronic aortic dissection with extension to bilateral subclavian arteries, bilateral common carotid arteries, right internal carotid artery, bilateral proximal external iliac arteries and simultaneous presentation of acute embolic stroke and seizure. The rarity of this case presentation and the presence of neurological features necessitated a high index of clinical suspicion to reach the definitive diagnosis. This study also demonstrates a unique situation requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is more common in males in their seventh decade of life and with a personal history of hypertension [1]. Other risk factors include smoking, obesity, and connective tissue diseases, and there is an agreement among many risk factors for this pathology and ischemic stroke [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more common in males in their seventh decade of life and with a personal history of hypertension [1]. Other risk factors include smoking, obesity, and connective tissue diseases, and there is an agreement among many risk factors for this pathology and ischemic stroke [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the onset manifests as severe and abrupt chest, abdominal, or interscapular pain [1,2]. Nevertheless, under specific conditions, aortic dissection can be an uncommon cause of ischemic stroke, and the onset may be marked by new neurological deficits [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative acute ischemic stroke (AIS) is one of important factors that affects the outcomes of surgical treatment and long-term post-operative survival in patients with acute type A aortic dissection (ATAAD) ( 1 ). Although ATAAD is a serious aortic disease that requires immediate surgical repair once diagnosed ( 1 , 2 ), The treatment of ATAAD with pre-operative AIS is more challenging. Many studies had proven that neurological damage caused by pre-operative AIS or cerebral malperfusion indicates a poor prognosis following ATAAD ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography angiography (CTA) and transthoracic echocardiography (TTE) have shown high sensitivity in the evaluation of high-risk plaque and vascular anatomy ( 5 ), and thus, are commonly used methods for the diagnosis of aortic dissection ( 6 ). Some studies have suggested about 5–10% of patients with ATAAD had an AIS before surgery, which was caused by the extension of the dissection into the common carotid arteries, thromboembolism or cerebral hypoperfusion ( 2 , 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%